2018
DOI: 10.1109/tvcg.2017.2744058
|View full text |Cite
|
Sign up to set email alerts
|

On the Treatment of Field Quantities and Elemental Continuity in FEM Solutions

Abstract: Fig. 1. 3D NACA wing example of vorticity before (left of the dashed line) and after (right) the application of our proposed approach.Abstract-As the finite element method (FEM) and the finite volume method (FVM), both traditional and high-order variants, continue their proliferation into various applied engineering disciplines, it is important that the visualization techniques and corresponding data analysis tools that act on the results produced by these methods faithfully represent the underlying data. To s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Later, Docampo-Sánchez et al proved that the Line-SIAC filter (L-SIAC), when applied to 2D and 3D simulation data, has all the properties of the SIAC filter [21], but is more computationally efficient than the traditional tensor-product-based SIAC filter in multiple dimensions. Jallepalli et al compared the commonly used data transformation methodologies to the L-SIAC filter and showed that the L-SIAC filter is a better tool for creating continuous visualization data [37]. This work, in part, motivates us to study its effect on downstream analysis with topological tools.…”
Section: Data Transformation Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, Docampo-Sánchez et al proved that the Line-SIAC filter (L-SIAC), when applied to 2D and 3D simulation data, has all the properties of the SIAC filter [21], but is more computationally efficient than the traditional tensor-product-based SIAC filter in multiple dimensions. Jallepalli et al compared the commonly used data transformation methodologies to the L-SIAC filter and showed that the L-SIAC filter is a better tool for creating continuous visualization data [37]. This work, in part, motivates us to study its effect on downstream analysis with topological tools.…”
Section: Data Transformation Methodologiesmentioning
confidence: 99%
“…For example, one can use topology to study vortex breakdown patterns [69], vortex merging [3], and shedding patterns. These techniques are built with the assumption of continuity in the data, but as presented in [37], one of the challenges associated with the visualization, and in this case the topological analysis, of HO-FEM fields (and their corresponding derived fields) is their lack of continuity at element interfaces. Fundamentally, topological analysis is based on extracting properties in a continuum: these properties are designed to be invariant to deformation but sensitive to topological events such as cutting or splitting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no prior work extracting ridge surfaces from FEM data, but Pagot et al find ridge lines on affine meshes via PVO and new seed finding and streamline routines [31]. Jallepalli et al's smoothing of finite element data could usefully complement the visualization methods we target [18].…”
Section: Related Workmentioning
confidence: 99%
“…We present preliminary work on extending the open-source compiler for a scientific visualization DSL [8,19,20], previously limited to regular grids, to also work on higher-order FEM data. Our long-term goal is to connect previous FEM visualization methods [11,18,25,[27][28][29][30][31][32] by simplifying how they can be expressed and combined in working code. Our current focus is just two kinds of visualizations, both involving computations on a discrete set of points: streamlines [11], and particle systems sampling surface features [25].…”
Section: Introductionmentioning
confidence: 99%